2010
DOI: 10.1007/s00436-010-2081-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to recombinant Brugia malayi pepsin inhibitor homolog (Bm-33) in patients with human lymphatic filariaisis

Abstract: Immune responses to recombinant Brugia malayi pepsin inhibitor homolog (rBm-33) were investigated in patients with human lymphatic filariasis (microfilaremics (MF) and chronic pathology (CP)) along with endemic normals (EN). Flow cytometric analysis (24 h) revealed CD4+ T cell activation in patients (MF and CP) compared to normals (EN), with increased expression of CD69 and diminished levels of CD62L and CD127. This was associated with an elevated expression of CD154 but not CD28 and CTLA4 in CP patients. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…rBm-33 is an aspartic protease inhibitor secreted by the human filarial parasite Brugia malayi and is believed to play a key role in host pathogenesis and immune modulation 18 . It was purified under denaturing conditions and refolded by step wise dialysis using buffers of pH ranging from 11 to 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rBm-33 is an aspartic protease inhibitor secreted by the human filarial parasite Brugia malayi and is believed to play a key role in host pathogenesis and immune modulation 18 . It was purified under denaturing conditions and refolded by step wise dialysis using buffers of pH ranging from 11 to 7.…”
Section: Discussionmentioning
confidence: 99%
“…Among these the best characterized one is the aspin (PI-3) from the nonfilarial nematode Ascaris suum that infects the pigs 15 . Similarly, an aspin (Bm-33) from the filarial nematode Brugia malayi has also been identified and the immunological characterizations have been reported [16][17][18] . In addition to this, the earlier studies from this laboratory reveal rBm-33 to be a human pepsin inhibitor 19 .…”
Section: Research Articlementioning
confidence: 99%
“…Studies with several experimental models suggested the role of CD 4 + T cells apoptosis in proliferative defect associated with the filarial patients [35,36]. We have previously shown using PBMCs that rBm33 induced unsustained early T cell activation in the MF individuals and one possibility for this could be the apoptosis of T cells in such individuals [12]. Similar studies have been carried out previously with live L3 microfilariae of B. malayi , which showed early Natural killer cell activation followed by NK cell apoptosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs were isolated from heparinized venous blood from five endemic normals by density centrifugation as described previously [12]. Cells obtained by Ficoll-Hypaque density centrifugation were suspended in complete RPMI 1640 medium and the cells were counted in hemocytometer by trypan blue exclusion and seeded in culture plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation